Anti-Inflammatory Effect of Caffeine on Muscle under Lipopolysaccharide-Induced Inflammation - Tuany Eichwald; Alexandre Francisco Solano; Jennyffer Souza; Taís Browne de Miranda; Liebert Bernardes Carvalho; Paula Lemes dos Santos Sanna; Rodrigo A. Foganholi da Silva; Alexandra Latini (MDPI AG, 2023)
Evidence has shown that caffeine administration reduces pro-inflammatory biomarkers, delaying fatigue and improving endurance performance. This study examined the effects of caffeine administration on the expression of inflammatory-, adenosine receptor- (the targets of caffeine), epigenetic-, and oxidative metabolism-linked genes in the vastus lateralis muscle of mice submitted to lipopolysaccharide (LPS)-induced inflammation. We showed that caffeine pre-treatment before LPS administration reduced the expression of Il1b, Il6, and Tnfa, and increased Il10 and Il13. The negative modulation of the inflammatory response induced by caffeine involved the reduction of inflammasome components, Asc and Casp1, promoting an anti-inflammatory scenario. Caffeine treatment per se promoted the upregulation of adenosinergic receptors, Adora1 and Adora2A, an effect that was counterbalanced by LPS. Moreover, there was observed a marked Adora2A promoter hypermethylation, which could represent a compensatory response towards the increased Adora2A expression. Though caffeine administration did not alter DNA methylation patterns, the expression of DNA demethylating enzymes, Tet1 and Tet2, was increased in mice receiving Caffeine+LPS, when compared with the basal condition. Finally, caffeine administration attenuated the LPS-induced catabolic state, by rescuing basal levels of Ampk expression. Altogether, the anti-inflammatory effects of caffeine in the muscle can be mediated by modifications on the epigenetic landscape.